Chronological implications of the nothrotheriid 'Xyophorus' (Mammalia, Xenarthra) from the Collón Curá Formation (Miocene of Patagonia, Argentina). (9th August 2019) - Brandoni, Diego; González Ruiz, Laureano; Reato, Agustina; Martin, Gabriel
Abstract: The specimen described herein and assigned to ' Xyophorus ' sp. (Mammalia, Xenarthra, Tardigrada) was collected in the locality Cerro Zeballos, northwestern Chubut Province, Argentina. The fossiliferous sediments bearing the specimen are correlated with Collón Curá Formation. The specimen has the features described for other members of ' Xyophorus ' (e.g. shape and size of the molariforms, relationship between diastema length, m1 and m2 length) and has a Diastema Length/Tooth Row Length index (DL/TRL index) of ca. 14, between that of ' X .' villarroeli (12.07) from the Mauri Formation, Bolivia (ca. 10.3 Ma) and that of ' X .' bondesioi (16.45) from Arroyo Chasicó Formation, Argentina (ca. 10–8.7 Ma). The relationship between DL/TRL index and age of the bearing sediments, would suggest a Tortonian age (late Miocene) for the deposits of Collón Curá Formation at Cerro Zeballos, which results in a 'younger age' compared to the middle Miocene age traditionally accepted for the Collón Curá Formation bearing the Colloncuran fauna sensu stricto . Although no absolute ages for Cerro Zeballos are available yet, the geographic proximity of Cerro Zeballos to Cushamen River (with levels dated at ca. 11.2 Ma) supports the tentative Tortonian age indicated by the presence of ' Xyophorus ' sp.